Persepsi Dukungan Organisasi dan Karakteristik Pekerjaan Terhadap Knowledge Sharing: Organizational Citizenship Behavior Sebagai Mediasi - Fitri Handayani; Sefnedi Sefnedi; Irwan Muslim (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
Organizational citizenshipxbehavior has been recognized as an important variable for every organization both in academicians and practitioners. Thexpurpose of this study is to investigate thexrole of organizatinal citizenship behavior as mediator onxthe relationshipxbetween perceivedxorganizational support, job characteritics and knowledge sharing. The number of respondents that could be used in this study was 37 employees of the CivilxServants inxthe Public Works andxPublic Housing Agencyxof the West Sumatra Region of Padang City. The resultsxof analysis showedxthat the perceived organizationalxsupport and jobxcharacteristics did not affect significantly knowledge sharing. Perceived organizationalxsupport wasxfound to have positive effect onxorganizational citizenship behavior and jobxcharacteristics did not influencexorganizational citizenship behavior. Furthermore,xorganizational citizenship behaviorxwas found to havexpositive effect on knowledgexsharing. In addition, organizationalxcitizenship behavior wasxproven to mediate thexrelationship between perceived organizationalxsupport and knowledge sharing.xHowever, it did notxmediate the relationship between jobxcharacteristics and knowledge sharing.